Causes of Asset Shortages in Emerging Markets - Chen, Jiaqian (IMF Working Papers; Working Paper ;, 2011)
We first illustrate that emerging markets (EMs) face a shortage of financial assets, with financial assets not growing as rapidly as domestic savings. We then estimate the asset shortage in EMs for 1995-2008. We develop a model that explains how asset shortage develop, and then econometrically estimate the causes of asset shortages. We conclude with policy implications.